The Influence of Social Media on the Motivation to Learn History of Grade XI Students in High School - Erlin, Erlin; Muhammad Aqil (Council: Education Journal of Social Studies, 2025)
This study was conducted with the intention of investigating the impact of utilizing the social media platforms Facebook and WhatsApp on the level of learning motivation in History among eleventh-grade students at SMA Negeri 1 Kupang. The research approach employed was quantitative. The data analysis technique in this study applied product-moment correlation to measure the strength of the influence and the significance of the relationship between the independent variable (social media usage) and the dependent variable (learning motivation), with reference to the r-table value at a 5% significance level. Based on the process of data processing and analysis using the product-moment formula, a comparison between the calculated r-value (r-hitung) and the table r-value (r-tabel) was obtained. The calculation results indicated that the calculated r-value was greater than the table r-value. Specifically, the calculated r-value was recorded at 0.602, while the table r-value at a 5% significance level was 0.361. Thus, it can be stated that the calculated r-value significantly exceeded the table r-value at a 5% significance level (0.602 > 0.361). These findings indicate that there is an influence between the use of social media and students' learning motivation, with a contribution of influence amounting to 36%. This clarifies that the utilization of social media Facebook and WhatsApp has an impact on students' learning motivation.